2018
DOI: 10.1155/2018/8625721
|View full text |Cite
|
Sign up to set email alerts
|

Hip Mobilization at Preterm Age May Accelerate Developmental Dysplasia Recovery

Abstract: Purpose Few studies have described mobilization approaches in developmental dysplasia of the hip (DDH). The present study describes the hip mobilization of a preterm infant (born at 33 6/7 weeks of gestational age) diagnosed with DDH. Design and Methods During the 43-day hospital stay, the infant was seen twice a week (ten sessions, 20 minutes each). All sessions included hip approximation maneuvers, with the hip positioned in abduction, lateral rotation and flexion, and lower limbs passive mobilization, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Publications on manual therapy or mobilizations for refractory DDH are extremely scarce. One study focused on the hip mobilization of a preterm infant diagnosed with DDH and suggested that an early treatment protocol aimed at optimal hip positioning may be beneficial for premature newborn patients with DDH [ 40 ]. Another case report discussed the effect of Korean medicine treatment, including acupuncture, electroacupuncture, cupping therapy, and chuna manual therapy for adult DDH over an eight-week period [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Publications on manual therapy or mobilizations for refractory DDH are extremely scarce. One study focused on the hip mobilization of a preterm infant diagnosed with DDH and suggested that an early treatment protocol aimed at optimal hip positioning may be beneficial for premature newborn patients with DDH [ 40 ]. Another case report discussed the effect of Korean medicine treatment, including acupuncture, electroacupuncture, cupping therapy, and chuna manual therapy for adult DDH over an eight-week period [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 Conversely, there is some early clinical evidence linking hip mobilization and accelerated recovery of DDH in preterm infants, indicating that active musculature and positioning may play a role in healthy hip development. 21 As parents continue to use baby gear, further research is needed to understand the musculoskeletal and biomechanical impacts of infant positioning for both DDH and healthy infants. A majority of commercial and scientific research is focused on the immediate safety (or the lack thereof) of infants in commercially available baby gear, specifically in the areas of preventing bodily injury and suffocation.…”
Section: Discussionmentioning
confidence: 99%
“…18 Yet, the role of inactive or active muscles to promote hip development in human infants has not been studied. Even in treating DDH with the Pavlik harness, the only contributive body position discussed in relation to closed reduction is passive supine lying, 19,20 and the roles of active musculature and positioning 21 are relatively unexplored.…”
mentioning
confidence: 99%